ANALYSIS OF SOCIAL VALUES IN THE SHORT STORY ABU SIR WA ABU QIR BY KAMIL KAILANI - Nudiyal Khair AS; Susiawati; Ahmad Sirfi Fatoni (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research is a literary research that aims to describe social values and the relevance of social values to character education values in the short story Abu Sir wa Abu Qir by Kamil Kailani. The data analysis technique used is data reduction, data presentation, and verification and conclusion. The data in this study are in the form of quotations or sentences contained in short stories, while the data source is the short story Abu Sir wa Abu Qir by Kamil Kailani. The data collection techniques in this research are reading and note-taking techniques. The results of this study show that the social values contained in this short story are in the form of moral values, vital values, legal compliance values, knowledge values, religious values, and aesthetic values. In addition, this study also found the relevance of social values to character education values in the form of honesty, hard work, creativity, and respect for achievement.